(untitled) (Pragyaratna प्रज्ञारत्न, 2025)
Motivation is an inner drive to achieve a set goal for learning. Motivation from the inside of a learner and motivation from the outside matter a lot to achieve success in learning. Quality education in higher education is possible through motivation of learners in learning. This research article was based on a qualitative method involving administrators and teachers directly in the investigation process. The research was conducted in three provinces, Koshi, Bagmati, and Gandaki, using a purposive sampling method. The population size was six campuses, both including government and community-based. Research design was conducted using an inductive method, and data were collected from the interview and focus group discussion method using open-ended questions. The study found that extrinsic factors are responsible to demotivate the students for their higher education completion. Environmental factors such as teacher- students communication, teacher’s update on subjective knowledge and participatory learning, role of student’s union, policy level decisions demotivate learners. It was found from the study that students demanded practical based curriculum in higher education, however, there were traditional and theoretical based curriculum. Students had deeply realized that four year courses for bachelor level were lengthy and monotonous for them, because they interacted with fast and immediate result oriented actions in their lives, mainly, in the digital devices. The higher education plan need to focus on the national requirements. It is an urgent need at the job market. Students friendly classroom teaching should be in priority to ensure participatory learning for quality education.